Should aspirin be replaced with ADP blockers and anti-GPVI to manage thrombosis? - Hafsa Khan; Tahira Ghulam; Naseer Ahmed; Muhammad Rafai Babar; Simon DJ Calaminus; Muhammad Zuhair Yusuf (Vascular Biology, 2023)
Platelets have a pivotal role in maintaining cardiovascular homeostasis. They are kept docile by endothelial-derived mediators. Aberration in haemostatic balance predisposes an individual to an elevated risk of a prothrombotic environment. Anti-platelet therapy has been a key component to reduce this risk. However, understanding how these medications affect the balance between the activation and inhibition of platelets is critical. There is no evidence that a key anti-platelet therapy – aspirin, may not be the most efficacious medicine of choice, as it can compromise both platelet inhibition and activation pathways. In this review, the rationale of aspirin as an anti-thrombotic drug has been critically discussed. This review looks at how recently published trials are raising key questions about the efficacy and safety of aspirin in countering cardiovascular diseases. There is an increasing portfolio of evidence that identifies that although aspirin is a very cheap and accessible drug, it may be used in a manner that is not always beneficial to a patient, and a more nuanced and targeted use of aspirin may increase its clinical benefit and maximize patient response. The questions about the use of aspirin raise the potential for changes in its clinical use for dual anti-platelet therapy. This highlights the need to ensure that treatment is targeted in the most effective manner and that other anti-platelet therapies may well be more efficacious and beneficial for CVD patients in their standard and personalized approaches.